Forage maize type influences on methane emissions, nutrient degradation, and fermentation profiles in ruminants - Farhad Parnian-khajehdizaj; Sajjad Moharramnejad (Scientific Reports)
Abstract The selection of forage maize (Zea mays L.) cultivars significantly impacts ruminant nutrition and environmental sustainability. This study evaluated four maize types (TWC647, SC704, D5, and a SC704 + D5 mixture) for their effects on methane emissions, nutrient degradability, and rumen fermentation using in vitro techniques. SC704 exhibited the highest gas production (236.8 ml/g DM), metabolizable energy (5.17 MJ/kg DM), and net energy for lactation (2.64 MJ/kg DM). TWC647 showed the highest degradability of dry matter, crude protein, and NDF. The SC704 + D5 mixture enhanced volatile fatty acid production but also resulted in the highest methane emissions (71.5 l/kg FOM). These findings emphasize the importance of cultivar selection in optimizing fermentation efficiency and reducing environmental impact.